A Review of Recent Advances in Spent Coffee Grounds Upcycle Technologies and Practices - Johnson, Kevin; Liu, Yang; Lu, Mingming (Frontiers in Chemical Engineering, 2022)
Coffee is the world’s second largest beverage only next to water. After coffee consumption, spent coffee grounds (SCGs) are usually thrown away and eventually end up in landfills. In recent years, technologies and policies are actively under development to change this century old practice, and develop SCGs into value added energy and materials. In this paper, technologies and practices are classified into two categories, those reuses SCGs entirely, and those breakdown SCG and reuse by components. This article provided a brief review of various ways to reuse SCGs published after 2017, and provided more information on SCG quantity, SCG biochar development for pollutant removal and using SCG upcycle cases for education. SCG upcycle efforts align the best with the UN Sustainable Development Goals (SDG) #12 “ensure sustainable consumption and production patterns”, the resultant fuel products contribute to SDG #7 “affordable and clean energy”, and the resultant biochar products contribute to SDG #6, “clean water and sanitation”.